2015
DOI: 10.1007/s11764-015-0501-8
|View full text |Cite
|
Sign up to set email alerts
|

The sexual health of female rectal and anal cancer survivors: results of a pilot randomized psycho-educational intervention trial

Abstract: Background Sexual dysfunction is a frequently reported consequence of rectal/anal cancer treatment for female patients. Purpose The purpose of this study was to conduct a small randomized controlled trial to assess the efficacy of a telephone-based, four-session Cancer Survivorship Intervention-Sexual Health (CSI-SH). Methods Participants (N = 70) were stratified by chemotherapy, stoma, and menopause statuses before randomization to CSI-SH or assessment only (AO). Participants were assessed at baseline, 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 36 publications
0
58
0
2
Order By: Relevance
“…Other researchers have similarly found that women with colorectal cancer reported worse sexual QOL [40] and greater psychological distress [7] compared to men, and that associations between sexual QOL and psychological distress were strongly linked for women [12]. Large well-designed research studies on sexual QOL in women with colorectal cancer could help clarify these associations, yet such studies are challenging to conduct because of low recruitment and inadequate survey completion [15, 18, 41]. Therefore, well-funded multi-site studies are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers have similarly found that women with colorectal cancer reported worse sexual QOL [40] and greater psychological distress [7] compared to men, and that associations between sexual QOL and psychological distress were strongly linked for women [12]. Large well-designed research studies on sexual QOL in women with colorectal cancer could help clarify these associations, yet such studies are challenging to conduct because of low recruitment and inadequate survey completion [15, 18, 41]. Therefore, well-funded multi-site studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…A simple brief validated sexual concerns screener [43, 44], could be used to identify patients with sexual or body image concerns and lead to timely treatments. Recent work offers guidance to clinicians to assess and refer patients who report sexual and body image concerns once identified [44, 45], and a few small intervention studies offer promising findings for interventions addressing sexual outcomes in samples of patients with colorectal cancer [18, 41]. Interventions are particularly needed to help ensure that the sexual concerns of women treated for cancer are addressed given that compared to men with cancer, women are significantly less likely to have sexual concerns discussed in their care [46].…”
Section: Discussionmentioning
confidence: 99%
“…Female rectal and anal cancer survivors have been found to experience substantial sexual difficulties related to vaginal strictures ostomy interference with sexual activity, soiling of personal and bed clothing, bowel and bladder incontinence, pain, and psychological distress (Sun et al, 2016;Sunesen et al, 2015), with prevalence rates of sexual concerns in the range of 19%-62% (DuHamel et al, 2016). Post-mastectomy and lumpectomy, women are faced with scarring, pain, and lost sensation in breast and/or nipple tissue (Falk & Dizon, 2013;Farthmann et al, 2016;Sekse et al, 2010).…”
Section: Effects Of Surgery On Sexual Wellbeingmentioning
confidence: 99%
“…In fact, clinical recommendations often suggest waiting until 4-6 weeks post RT to begin a dilation protocol (Bakker et al, 2014;Miles & Johnson, 2014). Owing to the close proximity of the vagina to the anus, it is not uncommon for anal cancer patients to experience vaginal stenosis after pelvic RT (DuHamel et al, 2016;Son, Law, Oh, & Apte, 2015) and also colo-rectal surgery (DuHamel et al, 2016;Hendren et al, 2005), therefore vaginal dilation may be appropriate; however, further evaluation of vaginal dilation outside of gyneoncology is needed. Owing to the close proximity of the vagina to the anus, it is not uncommon for anal cancer patients to experience vaginal stenosis after pelvic RT (DuHamel et al, 2016;Son, Law, Oh, & Apte, 2015) and also colo-rectal surgery (DuHamel et al, 2016;Hendren et al, 2005), therefore vaginal dilation may be appropriate; however, further evaluation of vaginal dilation outside of gyneoncology is needed.…”
Section: Vaginal Dilationmentioning
confidence: 99%
See 1 more Smart Citation